2019
DOI: 10.1007/s00432-019-02899-y
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the characteristics and treatment outcomes of patients with non-small cell lung cancer treated with anti-PD-1 therapy in real-world practice

Abstract: Purpose Immune checkpoint inhibitors (ICI) have shown marked responses in patients with non-small cell lung cancer (NSCLC) in clinical trials. However, because such trials comprise cohorts selected based on specific criteria, it is unclear if their results represent routine clinical practice. Methods We examined 155 patients with advanced NSCLC who were administered either nivolumab or pembrolizumab at Yonsei Cancer Center, Korea between March 2014 and January 2019. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 33 publications
1
50
1
Order By: Relevance
“…Conventional treatment of liver metastases consists of systematic and palliative therapy (39). With the advent of immunotherapy with revolutionary efficacy, however, several studies have demonstrated liver metastases as an independent poor prognostic factor of immunotherapy for NSCLC (11)(12)(13). Patients with liver metastases exhibited significantly shorter OS (mOS, 3.12 months) and PFS (mPFS, 1.35 months) compared with those without liver metastases (mOS, 11.37 months; mPFS, 3.75 months) in a retrospective study, with an overall response rate (ORR) of 22.5% (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional treatment of liver metastases consists of systematic and palliative therapy (39). With the advent of immunotherapy with revolutionary efficacy, however, several studies have demonstrated liver metastases as an independent poor prognostic factor of immunotherapy for NSCLC (11)(12)(13). Patients with liver metastases exhibited significantly shorter OS (mOS, 3.12 months) and PFS (mPFS, 1.35 months) compared with those without liver metastases (mOS, 11.37 months; mPFS, 3.75 months) in a retrospective study, with an overall response rate (ORR) of 22.5% (40).…”
Section: Discussionmentioning
confidence: 99%
“…In a real-world cohort investigating the efficacy of nivolumab in patients with NSCLC, the presence of liver metastases predicted worse overall survival (4.0 vs. 9.0 months, p < 0.001), while pulmonary metastasis conferred a better outcome (8.8 vs. 5.6 months, p = 0.004) (10). Among different metastatic sites, bone, brain, and liver metastases were generally regarded as independent poor prognostic factors for ICI therapies (11)(12)(13)(14). However, these results did not compare the efficacy of ICIs with other conventional treatments.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies has supported this hypothesis by showing favorable outcomes for patients with non-small cell lung cancer (NSCLC) and melanoma who developed various irAEs in response to immune checkpoint inhibition [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, a definite conclusion has not been drawn based on the findings from each single study, as contradictory results exist [23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, monoclonal antibodies such as pembrolizumab and nivolumab targeting the programmed death 1 (PD-1) receptor and its ligand programmed death-ligand 1 (PD-L1), facilitate a patient’s own T cells to kill tumors, resulting in remarkable antitumor activity in NSCLC patients 5 , 6 . Recent clinical trials 7 11 and real-world data 12 14 have shown that anti-PD-1/PD-L1 immunotherapy results in robust disease control, long-term survival, and improved quality of life in advanced NSCLC patients. Unfortunately, immunotherapy can only benefit a subgroup of patients, and demonstrates response rates of only 17%–21% 15 .…”
Section: Introductionmentioning
confidence: 99%